Role of Selective Neck Dissection in Primary T1, T2, N0 Neck Oral Tongue Carcinoma (Bangladesh Journal of Otorhinolaryngology, 2021)
Background: Oral tongue is one of the common site for carcinoma. 22% to 39% of oral cancer develops at this site. The high incidence of cervical lymph node metastasis, occult cervical metastasis, Provide a logical basis for treatment of the neck. The aim of this is study was to find out the importance of selective neck dissection in primary T1, T2, N0 Neck Oral Tongue Carcinoma.Methods: This cross-sectional study was conducted in the Department of Otolaryngology- Head & Neck Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka Medical College Hospital and National Institute of ENT, Dhaka. Thirty cases of primary T1, T2, N0 Neck Oral Tongue Carcinoma with inclusion criteria was enrolled as a study sample. Patients were evaluated by a complete clinical head and neck examination as well as Imaging (MRI) of the primary tumor and neck. All the data were compiled and sorted properly and the numerical data were analyzed statistically. The results were expressed as percentage and mean ± SD. Chi-square (x2) test or Fisher’s Exact test was done for comparison of data presented in categorical value and p value